The Role of Employers' Unions in Industrial Relations in Malaysia - Hassan, Kamal Halili (Kanun: Jurnal Undang-undang Malaysia, 2025)
This paper analyses the role of employer unions in the context of industrial relations in Malaysia. Employer unions are coalitions of employers operating in various industrial sectors across the country. There are unions or federations representing employers across diverse economic sectors, as well as associations whose members are specifically involved in particular or similar business activities. This paper focuses on their roles in various activities, such as contributing to legislative development, engaging in collective bargaining, and resolving industrial disputes. The analysis begins with the question of the role played by employer unions, particularly in the formulation of national industrial relations policies. It raises the question: Do employer unions always oppose or cooperate with the government in formulating industrial relations policies and legislation? Through a qualitative approach, this paper analyses trends and patterns of action among employer unions in Malaysia’s industrial relations by referencing statistics, association reports, books, and journal articles. The findings reveal that employer unions contribute meaningfully to national labour policies, whether through their roles in drafting or amending new legislation, engaging in collective bargaining, or participating in dispute resolution processes. Keywords: Employer associations, trade unions, industrial relations, collective bargaining, trade dispute Full text: PDF